1986
DOI: 10.1016/s0735-1097(86)80419-3
|View full text |Cite
|
Sign up to set email alerts
|

When is the vectorcardiogram superior to the scalar electrocardiogram?

Abstract: The clinical usefulness of the vectorcardiogram is well documented by the numerous reports published in the last 3 decades. It has been found more reliable than the electrocardiogram for the diagnosis of atrial enlargement and right ventricular hypertrophy. It is more sensitive than the electrocardiogram in the recognition of myocardial infarction, especially if the infarction is inferior or if it occurs in the presence of left bundle branch block or left anterior hemiblock. It is helpful in the diagnosis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 82 publications
0
17
0
1
Order By: Relevance
“…The VCG has a greater sensitivity than the ECG in detecting atrial enlargements 4 and greater sensitivity and specificity than the ECG in the diagnosis of left ventricular enlargement (LVE). Abbott-Smith et al made vectorcardiograms in 100 patients carriers of LVE confirmed in the necropsy 5 and concluded that the VCG was capable of diagnosing 50% of the cases, with 11.7% of false positives.…”
Section: Vectormentioning
confidence: 99%
“…The VCG has a greater sensitivity than the ECG in detecting atrial enlargements 4 and greater sensitivity and specificity than the ECG in the diagnosis of left ventricular enlargement (LVE). Abbott-Smith et al made vectorcardiograms in 100 patients carriers of LVE confirmed in the necropsy 5 and concluded that the VCG was capable of diagnosing 50% of the cases, with 11.7% of false positives.…”
Section: Vectormentioning
confidence: 99%
“…Since the right ventricle (RV) has a lower mass than the left ventricle (LV) in both rats (5,21) and humans (22), RV electrical activity is largely masked by the LV electrical activity under normal conditions (28). We hypothesized that an increasing RV workload, elicited by progressive loss of pulmonary vasculature in PAH, would trigger a corresponding degree of RV hypertrophy, inducing threedimensional body surface ECG changes (7). We chose to investigate the evolution of three-dimensional body surface ECG abnormalities in a rat model of pulmonary hypertension.…”
mentioning
confidence: 99%
“…Edenbrandt L. et al also concluded that VCG proved to be more efficient than ECG for Superior AMI [6]. Te-Chuan Chou asserts that VCG provides better results in detection and diagnosis of atrial enlargements [7], by other hand, Abbott-Smith et al referring that VCG is better than ECG for left ventricular enlargement detection [8]. VCG also is superior to ECG in detection of ventricular chamber enlargement due to electrical inactive areas [9].…”
Section: B Vcg Versus Ecgmentioning
confidence: 99%